Analysis of Panel and Pile Verticality and Overlap in a Project Information Management System - Jamey Rosen; Georgette Hlepas (Deep Foundations Institute, 2021)
Verticality data collected from panel and pile elements of seepage barrier walls describe the shape and position of those elements in three dimensions. These data are used to determine if a barrier wall is constructed as designed and if it meets the owner specifications with respect to tolerance (i.e., if each element is sufficiently close to vertical) and overlap (i.e., do adjacent elements overlap sufficiently to prevent leakage). Contractors use verticality data to confirm that their work matches the design, and owners use verticality data to verify the contractor’s work and confirm that specified criteria were met. Project Information Management Systems (PIMS) technology has been applied to the management, visualization, and analysis of verticality data. This paper will provide examples of how contractors and owners have used a PIMS to compile and synthesize data collected during excavations (e.g., from Cutter Soil Mixer and Hydromill drill rig telemetry), and from measurements of completed excavations (e.g., using the Koden ultrasonic tool), and used those data to model excavation geometry. We will present case studies of using these models to estimate backfill placement volumes, and to evaluate the verticality tolerance and overlap between elements.